Creation of the Polish version and adaptation of the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire-Endometrial Cancer Module (QLQ-EN24) - Stukan, Maciej; Zalewski, Kamil; Grabowski, Jacek P.; Mardas, Marcin; Jones, Steven; Pietrzak-Stukan, Małgorzata; Dudziak, Mirosław (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study: The purpose of this study was to create and introduce a Polish version of the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire for Endometrial Cancer (QLQ-EN24). Material and methods: The translation procedure described by the EORTC was adopted; this comprised two independent forward translations of the original English questionnaire into Polish, two independent backward translations from Polish to English and pilot testing conducted on 12 patients with diagnosed endometrial cancer. They were asked whether there was any difficulty in answering, confusion while answering, or difficulty in understanding the questions, and if the patients themselves would have framed the questions in a different way. Results : During the process of translation, discussions and text corrections were performed by medical experts and native English speakers. Some sentences or phrasing were adopted from other EORTC questionnaires for different diseases. After pilot testing, further text corrections were adopted according to patients’ comments. These involved wording, sentence structure, and text editing (font size, bolding). Conclusions : The final version of the Polish EN24 questionnaire has been approved by the EORTC Translational Office. It is available on the EORTC web page now.